UNLOCKING POTENTIAL: THEME-BASED LEARNING TO IMPROVE NON-ENGLISH MAJORS’ READING AND WRITING SKILLS - Putra, Hedyan; Sekewael, Mansye (English Review: Journal of English Education, 2025)
This study explores the effectiveness of theme-based learning in enhancing English reading comprehension and writing skills among non-English majors, specifically accounting students at the State Polytechnic of Ambon. Using a quasi-experimental pretest-post-test control group design, 50 fourth-semester students were divided into experimental and control groups, with the experimental group receiving 20 instructional sessions using the Theme-Based Model of Content-Based Instruction (CBI). The results demonstrated significant improvements in reading comprehension and writing skills in the experimental group, with 36% of students achieving "Excellent" scores in reading comprehension post-tests, compared to none in the pretest. Writing skills showed improvement across content, organization, grammar, word choice, and mechanics. Statistical analyses, including Paired Sample t-tests and regression analysis, confirmed the efficacy of this approach, which mainly benefited reading comprehension components like inference, sequencing, and vocabulary. At the same time, grammar and structure were pivotal in writing improvement. These findings highlight the importance of integrating theme-based learning into English curricula for non-English majors to address the gap between language proficiency and professional learning needs.